1998
DOI: 10.1037/0022-006x.66.5.761
|View full text |Cite
|
Sign up to set email alerts
|

Schedule of voucher delivery influences initiation of cocaine abstinence.

Abstract: This study examined whether voucher delivery arrangements affect treatment outcome. First, 90 cocaine-dependent adults were randomly assigned to behavioral counseling or counseling plus vouchers for cocaine-free urine samples. The value of each voucher was low at the beginning but increased as the patient progressed (Voucher Schedule 1). Voucher Schedule 1 produced no improvements relative to counseling only. Next, 23 patients received vouchers on either Voucher Schedule 1 or Voucher Schedule 2. Voucher Schedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
52
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 26 publications
6
52
0
Order By: Relevance
“…However, numerous clinical trials have since demonstrated the efficacy of voucher-based contingency management in a broad range of settings and populations. These include methadone maintenance settings for cocaine-dependent substance users in large urban areas (22), homeless substance users with significant levels of psychopathology (23), and freebase cocaine users (24).…”
Section: Behavioral Treatmentsmentioning
confidence: 99%
“…However, numerous clinical trials have since demonstrated the efficacy of voucher-based contingency management in a broad range of settings and populations. These include methadone maintenance settings for cocaine-dependent substance users in large urban areas (22), homeless substance users with significant levels of psychopathology (23), and freebase cocaine users (24).…”
Section: Behavioral Treatmentsmentioning
confidence: 99%
“…Dozens of well-controlled experiments in community drug treatment programs have demonstrated that reinforcing treatment attendance or negative urine drug screens with vouchers or gift certificates can produce significant improvements in outcomes (e.g., Higgins et al, 1991;Kirby, Marlowe, Festinger, Lamb, & Platt, 1998;Silverman et al, 1998Silverman et al, , 2007. Recent meta-analyses reported moderate to large effects of such interventions on abstinence from drug use (Griffith, Rowan-Szal, Roark, & Simpson, 2000;Lussier, Heil, Mongeon, Badger, & Higgins, 2006;Prendergast, Podus, Finney, Greenwell, & Roll, 2006).…”
mentioning
confidence: 99%
“…Providing higher magnitude reinforcement for achievements early in treatment could capitalize on these characteristics to optimize outcomes. Higher magnitude reinforcement might compete more effectively against the naturally occurring contingencies that operate in clients' lives to maintain their involvement in drug abuse and crime (e.g., Kirby et al, 1998;Skinner, 1938). On the other hand, drug offenders might be more likely to make illadvised acquisitions (e.g., items that can be readily converted to cash) if they receive highmagnitude reinforcement prior to establishing a stable interval of sobriety.…”
mentioning
confidence: 99%
“…Petry, Alessi, Marx, Austin, & Tardif, 2005) or under a periodic schedule (Kirby, Marlowe, Festinger, Lamb, & Platt, 1998). For example, Petry and her colleagues have obtained good treatment outcomes when drug abstinence was reinforced with a chance of winning a variety of tangible prizes (e.g., Petry, 2000;Petry et al, 2004;Petry & Martin, 2002).…”
Section: Relative Costs and Benefits Over The Status Quomentioning
confidence: 99%